Fecal microbiota transplantation as a potential way to eradicate multiresistant microorganisms. (2018) - Dias, Cátia; Pipa, Sara; Duarte-Ribeiro, Filipa; Mota, Margarida
Abstract: Multiresistant microorganism infection often can produce a life-threatening situation. We report two cases in which fecal microbiota transplantation used for the treatment of recurrent Clostridium difficile infection were effective in eradicating colonization by carbapenemase-producing Enterobacteriaceae . The presented cases illustrate the potential benefit of fecal microbiota transplantation in resolution of asymptomatic carrier states of multiresistant microorganisms, suggesting the need for further investigations with a view to their applicability in this area.